COMMUNICATION PATTERNS BETWEEN TEACHERS AND STUDENTS IN THE TEACHING AND LEARNING PROCESS (SMK ISLAMIC CENTER BAITURRAHMAN) - M. Rikza Chamami; Natasya Ayu Amalia (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to examine and analyze communication patterns between teachers and students in the teaching and learning process at SMK Islamic Center Baiturrahman. Communication between teachers and students plays a crucial role in creating an effective and conducive learning atmosphere. This study uses a descriptive qualitative approach with observation, interview, and documentation methods as data collection techniques. The results of the study indicate that communication patterns in this school run in an open, participatory, and religious atmosphere. Teachers not only act as conveyors of information, but also as guides and motivators who establish positive interpersonal relationships with students. Factors such as teaching style, student motivation, and school environmental support influence the smoothness of communication. Effective communication has been shown to improve students' understanding of the subject matter and strengthen their character and discipline. This study concludes that good communication patterns between teachers and students contribute directly to the achievement of learning outcomes and the formation of students' character holistically.